Morphometric and molecular characterisation of four new Ceratomyxa species (Myxosporea: Bivalvulida: Ceratomyxidae) from fishes off Lizard Island, Australia - Gunter, Nicole L; Burger, Micke A. A; Adlard, Robert D (Folia parasitologica, 2010)
Four new species of Ceratomyxa Thélohan, 1892 are described from the gall bladders of fishes collected off Lizard Island, Australia. These species are characterised using a combination of morphometric and molecular data. Ceratomyxa bartholomewae sp. n. is described from Hyporhamphus dussumieri (Valenciennes) (family Hemirhamphidae); C. koieae sp. n. is described from Sphyraena forsteri Cuvier (family Sphyraenidae); C. pantherini sp. n. is described from Bothus pantherinus (Rüppell) (family Bothidae) and C. reidi sp. n. is described from Chaetodon vagabundus Linnaeus (family Chaetodontidae). A fifth species from Zebrasoma veliferum (Bloch) (family Acanthuridae) is also reported but due to limited material is not formally described here.
Keywords: Austrálie; druhová specificita; Fish Diseases; fylogeneze; Phylogeny; Gallbladder; Pacific Ocean; Myxozoa; Species Specificity; ryby; Fishes; Animals; parazitární nemoci u zvířat; zvířata; nemoci ryb; Parasitic Diseases, Animal; žlučník; Tichý oceán; Financing, Organized; financování organizované; Australia